2010
DOI: 10.1002/mc.20660
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of programmed cell death 4 by inflammatory conditions contributes to the generation of the tumor promoting microenvironment

Abstract: Ample evidence has shown key roles of inflammation in tumor promotion and carcinogenesis, and tumor-associated macrophages are known to promote tumor growth and dissemination. Programmed cell death 4 (Pdcd4) is a novel tumor suppressor, and although various studies have revealed that the functions and expression mechanisms of Pdcd4 in tumor promotion, those in regard to inflammation remain unclear. In the present study, we examined whether inflammatory stimuli regulate Pdcd4 expression. 12-O-tetradecanoylphorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…Its role in the regulation of cell proliferation is controversial, i.e., while egr2 was shown to be induced in cells overexpressing tumor suppressor PTEN (Matsushima-Nishiu et al 2001), it also appears to induce the prosurvival protein Mcl1 and to stimulate proteasomal degradation of the proapoptotic protein Bim (Bradley et al 2008). Thus, while egr2 translation is enhanced under conditions which we have previously shown to be protumorigenic (Yasuda et al 2010;Schmid et al 2011), the function of egr2 in this setting remains to be elucidated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Its role in the regulation of cell proliferation is controversial, i.e., while egr2 was shown to be induced in cells overexpressing tumor suppressor PTEN (Matsushima-Nishiu et al 2001), it also appears to induce the prosurvival protein Mcl1 and to stimulate proteasomal degradation of the proapoptotic protein Bim (Bradley et al 2008). Thus, while egr2 translation is enhanced under conditions which we have previously shown to be protumorigenic (Yasuda et al 2010;Schmid et al 2011), the function of egr2 in this setting remains to be elucidated.…”
Section: Discussionmentioning
confidence: 86%
“…Briefly, we used supernatants of activated U937 monocytederived macrophages (CM) which we have previously shown to contain significantly elevated protein levels of the proinflammatory mediators TNFa, IL-6, and IL-8 as compared to supernatants of undifferentiated U937 monocytes (Ctr) (Schmid et al 2011). Additionally, CM enhanced AP1-transactivation and degradation of the tumor suppressor Pdcd4 (Yasuda et al 2010), thereby providing evidence for the induction of a protumorigenic program in MCF7 cells.…”
Section: Inflammatory Conditions Provokes Translational Changes Of Spmentioning
confidence: 99%
“…9 On the contrary, some other studies suggest that PDCD4 downregulation increases LPS-induced expression of proinflammatory mediators, such as TNF-a in RAW264.7 cells. 10 Therefore, the exact role of PDCD4 in inflammation remains to be elucidated. The present in vivo study first indicates that compared with WT mice, PDCD4-deficient mice secrete more inflammatory cytokines and have more obvious hepatocyte apoptosis and necrosis in response to LPS/D-GalN, which suggests an inhibitory function of PDCD4 in LPS/D-GalN-induced acute liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other reports have shown that knockdown of PDCD4 increases TNF-a protein production in LPS-stimulated RAW264.7 macrophages and indicate that PDCD4 is an anti-inflammatory factor. 10 Therefore, the exact role of PDCD4 in inflammatory diseases remains to be investigated.…”
mentioning
confidence: 99%
“…PDCD4 suppresses the induction of inflammatory mediators of TNF-a and IL-10. 30,31 Inflammatory environment in vivo can induce downregulation of PDCD4 proteins. These results suggest PDCD4 is likely to be an antiinflammatory factor.…”
Section: Target Genes and Proteins Expression In Test And Control Groupsmentioning
confidence: 99%